Educational experience in the community pharmacy setting - Jiménez Herrera, Luis Guillermo (2024)
Community pharmacies are centers that offer pharmaceutical services, and these must be immersed in a safe environment for the patient. The objective was to assess the opinion of people in community pharmacies regarding patient safety through a pharmaceutical educational experience. An educational experience was carried out that included theoretical training sessions, and of eleven Pharmacy students to carry out a qualitative, exploratory, and cross-sectional investigation with the questionnaire of the Agency for Research and Quality of Health Care with several sections (work, communication and rhythm, safety and response to errors, documentation) related to patient safety. Community pharmacies were visited to achieve the participation of people in a voluntary manner that makes the responses anonymous and confidential. The participation of 31 people was reached, including pharmacists, technicians, students, assistants, and clients in 29 community pharmacies in six provinces of Costa Rica. In general, people assigned 81% to the safety of patients in the community pharmacy, the perception is positive towards most aspects. The deficiency of standardized operating procedures in the work of the community pharmacy stands out. The pharmaceutical educational experience favors student learning and obtaining information that highlights the strengths of community pharmacy action that requires addressing weaknesses to achieve a culture of patient safety. Keywords: pharmacy, community, education.